High intensity long interval sets provides similar enjoyment as continuous moderate intensity exercise. The Tromsø Exercise Enjoyment Study - Sagelv, Edvard Hamnvik; Hammer, Tord; Hamsund, Tommy; Rognmo, Kamilla; Pettersen, Svein Arne; Pedersen, Sigurd (Frontiers in Psychology, 2019)
Source at https://doi.org/10.3389/fpsyg.2019.01788. Objective : High intensity interval exercise sessions with interval sets over 3 min may provide superior cardiorespiratory fitness benefits. To our knowledge, the exercise enjoyment of interval sets over 3 min is not yet elucidated. The aim of this study was to examine exercise enjoyment following one session with four intervals of 4 min high intensity exercise (HIIE) versus one session of 45 min moderate intensity continuous exercise (CE) in iso-caloric conditions using a randomized crossover design. Methods : Seven young healthy participants were recruited to undergo two different exercise sessions in a randomized order: (1) 4 × 4 min intervals at >90% of maximum heart rate (HR max ) with 3 min of rest between interval sets, and (2) 45 min CE at 70% of HR max . Peak oxygen uptake and HR max were evaluated prior to the experiment. The participants reported their perceived exercise enjoyment using the 18-item physical activity enjoyment scale (PACES) questionnaire and their rating of perceived exertion (RPE) using Borg’s 6–20 scale. Results : There was no difference in the PACES score between the high intensity interval exercise session [median: 95.5 (inter-quartile range: 21.8)] and the moderate intensity CE session [91.0 (13.5), p = 0.36, r = −0.22]. The participants reported a higher RPE in the high intensity interval exercise session [16.5 (2.0)] compared with the CE session [9.0 (2.0), p = 0.01, r = −0.88]. Conclusion : Similar exercise enjoyment was reported following four high intensity intervals of 4 min compared with a moderate intensity CE session in this randomized crossover study with iso-caloric conditions. If enjoyment is a mediating factor for engaging in exercise, one should expect a similar probability of exercise adherence following high intensity 4 min intervals and continuous moderate intensity exercise when prescribing aerobic exercise as preventive medicine.